2023
DOI: 10.3390/en16135004
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Reactive Power Dispatch in Electric Transmission Systems Using the Multi-Agent Model with Volt-VAR Control

Alex Chamba,
Carlos Barrera-Singaña,
Hugo Arcos

Abstract: The optimal dispatch of reactive power is a fundamental task in the operational planning of electrical power systems. This task aims to minimize active power losses and improve voltage levels within the electrical power system. This paper presents the application of the particle swarm optimization methodology to achieve optimal reactive power dispatch. The methodology’s performance is demonstrated by its high processing speed and the results obtained through a comprehensive global search for reactive power dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Considering that there is no disconnection of any transmission line, a reduction in losses can be observed in lines (6)(7)(8)(9)(10)(11)(12), (6-13), (9-10), (9-14), (10)(11), (12)(13), (6)(7)(8)(9)(10)(11), (4-5), and (13)(14). In line (3)(4), the losses are lower compared to the rest of the lines in the first case study.…”
Section: Base Case Lossesmentioning
confidence: 82%
See 2 more Smart Citations
“…Considering that there is no disconnection of any transmission line, a reduction in losses can be observed in lines (6)(7)(8)(9)(10)(11)(12), (6-13), (9-10), (9-14), (10)(11), (12)(13), (6)(7)(8)(9)(10)(11), (4-5), and (13)(14). In line (3)(4), the losses are lower compared to the rest of the lines in the first case study.…”
Section: Base Case Lossesmentioning
confidence: 82%
“…When analyzing the different cases, it is evident that losses are more pronounced during random contingencies. Regarding transmission lines (1-2), (1-5), (2-3), (2-4), (2-5), (3)(4), and (4-5), it is observed that the losses are minimal when a change in the system topology is made through OTS, or rather, they have less impact. ].…”
Section: Base Case Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactive power dispatch in power systems is performed traditionally by minimizing the active power losses of the lines [22], and others propose to minimize the generation costs [23,24], where the minimization of the costs is associated with the reactive power dispatch of the generators.…”
Section: Reactive Power Dispatchmentioning
confidence: 99%